Actuation characteristics and applications of piezoelectric materials and ionic polymer-metal composites - Zhang, Lei (2008)
This thesis focuses on the actuation characteristics of piezoelectric materials and ionic polymer-metal composites (IPMCs) for biomedical applications. The piezoelectric actuated plates and shells on elastic foundation are investigated. Analytical solutions are obtained to describe the structural responses under the piezoelectric actuation. The optimal placement of a piezoelectric actuator on the plate and shell in terms of maximizing excitation is investigated and solved by proposing a simple and general procedure. The actuation mechanism of the IPMC is investigated. Explicit bending moment expressions are derived to account for the bending capacity of the IPMC under both the static and dynamic electric potentials. Three IPMC based biomedical prototypes, i.e., an IPMC beam on human tissues, an IPMC ring with elastic medium and an IPMC cylindrical shell with contained flowing fluid are developed based on the bending moment expressions. The output effects, i.e., the pressure on the tissues or organs and the velocity changes in flowing fluid, have been obtained analytically.